THE IMPLEMENTATION OF PORTFOLIO WITH TEACHERâS FEEDBACK TO IMPROVE STUDENTSâ WRITING - Budiardi, Alfian Cahyo (Jurnal Pendidikan Saintifik, 2014)
English Department Faculty Of Teacher Training And Education University Of Muhammadiyah Malang   ABSTRACT: This research aims to To confirm the implementation of portfolio with teacher feedbacks can improve the students’ writing ability. the appropriate design for this research is Classroom Action Research (CAR). CAR is such an approach in a research which is classroom based research or schools to solve the problems which happen in a certain classroom. n doing this research, XI IPA-1 students of SMAN 3 Malang are chosen as the subject since they have some problems which need to be improved. They are given the treatment which is portfolio with teacher’s feedback to improve their writing. The treatment is implemented continuously to them. This research is conducted in two cycles, first cycle and second cycle  which each cycle consists of four steps. Those steps are planning, implementation, observation, and evaluation or reflection. esults of data analysis showed   after the implementation of the treatments among cycle one and two, there is no students who achieve lower score than the passing grade (KKM) which is determined by the school as 80. It is different from the situation before the treatments are given in which there are 13 students who have lower score than KKM and 6 students have equal score to KKM.                              Keywords: writing, implementation portfolio